Language Maintenance at the Javanese Family in Bukit Malintang District - Ningsih, Sudarti Rahayu; Harahap, Lenni Marlina (SALTeL Journal (Southeast Asia Language Teaching and Learning), 2019)
This research was intended to investigate the types, the factors, and the reasons of language maintenance. Research design in this study was in case study approach by using descriptive qualitative method. The data were the intensity of using utterances of Javanese language in transcript of the interview to the Javanese early family in language maintenance. The data source of this research was intermarriage Javanese family. Techniques of collecting the data in this research were observation, interview and documentation. Data were analysed by using Miles, Huberman, and Saldana’s theory with the processes of data condensation, data display, and conclusion drawing/verification. Result of the research showed that the language maintenance was based on active language maintenance type. Factor of language maintenance was the loyalty to maintain its language although it face. The reason of language maintenance was to keep ethnic identity. Meanwhile, it did not happen to their fourth child, the child could not maintain Javanese language, he just know that Javanese language as their language should be known as the history.